2019
DOI: 10.1177/1471301219868619
|View full text |Cite
|
Sign up to set email alerts
|

Graphic designed bedroom doors to support dementia wandering in residential care homes: Innovative practice

Abstract: Dementia-friendly designs are important in residential care homes but an aspect that remains neglected is the potential role of door designs in promoting wayfinding. A pilot project in NSW, Australia, tested the effects of unique room door designs for a small group of individuals living with dementia in a residential care home. Internal doors were transformed using a giant adhesive poster created by a commercial graphic designer. The poster replicated the look of traditional front doors, including a range of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 8 publications
0
15
0
2
Order By: Relevance
“…Hung et al 20 To examine the influences of dining room renovations and enhanced mealtime practices on the quality of residents' experiences and staff practices • The newly built cluster arrangement scored higher in all eight areas of the PEAP instrument compared with the scores of the facility before renovation • The three areas of (1) maximize awareness and orientation, (2) provision of privacy, and (3) facilitation of social contact had the highest variation in the pre-and post-renovation PEAP scores • The general reaction from the staff was that replacing the prominent nurses' station with the aviary reduced the institutional ambiance in the facility However, some staff members were concerned that residents sitting near the aviary were engaged in passive behavior Nolan et al 18 To evaluate the effect of an environmental modification designed to provide residents of a special care unit with easy access to information about mealtimes in this theme in some of its dimensions. There are interventions to reduce ambulation and excessive stimulation of the patient, [5][6][7][8] attempts to prevent exit or escape, 6,8-10 door testing, 11,12 and improvements in orientation/location. 6,7, [13][14][15][16][17] But how do people with dementia know where to go?…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hung et al 20 To examine the influences of dining room renovations and enhanced mealtime practices on the quality of residents' experiences and staff practices • The newly built cluster arrangement scored higher in all eight areas of the PEAP instrument compared with the scores of the facility before renovation • The three areas of (1) maximize awareness and orientation, (2) provision of privacy, and (3) facilitation of social contact had the highest variation in the pre-and post-renovation PEAP scores • The general reaction from the staff was that replacing the prominent nurses' station with the aviary reduced the institutional ambiance in the facility However, some staff members were concerned that residents sitting near the aviary were engaged in passive behavior Nolan et al 18 To evaluate the effect of an environmental modification designed to provide residents of a special care unit with easy access to information about mealtimes in this theme in some of its dimensions. There are interventions to reduce ambulation and excessive stimulation of the patient, [5][6][7][8] attempts to prevent exit or escape, 6,8-10 door testing, 11,12 and improvements in orientation/location. 6,7, [13][14][15][16][17] But how do people with dementia know where to go?…”
Section: Resultsmentioning
confidence: 99%
“…One study increased the possibilities of natural light 7 and another reinforced the light during the day and progressively decreased the light at night, together with the streaming of soft music. 5 The results showed that the number of episodes of agitation and the average duration of episodes of wandering decreased significantly. In addition to this intervention with music, another study indicated that, regardless of the severity of dementia, exposure to live music is related to positive clinical white color.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…(FLEMING, BENNETT, 2017) Figura 20 Adaptação da porta do quarto. Foram projetadas 11 portas com diferentes cores, desenhos e números (VARSHAWSKY, 2019) 97…”
Section: Lista De Figurasunclassified
“…Mas, além disso, devem sinalizar (dar pistas) o cômodo por detrás. A personalização de portas dos quartos demonstrou bons resultados na redução de comportamentos como o andar errante e a tentativa de saídas e na melhora da orientação espacial (VARSHAWSKY, 2019). Error!…”
Section: Situar O Idoso Sobre Qual Ambiente Ele Estáunclassified